PENGARUH PEMUPUKAN P DAN GREEN MANURE LEGUMINOSA BUNGA TELANG TERHADAP PERTUMBUHAN DAN HASIL JAGUNG PULUT ARUMBA (Zea mays Ceratina var. Arumba) - Galih Ainur Rofik; Didik Utomo Pribadi; Felicitas Deru Dewanti (BPFP Universitas Bengkulu, 2025)
[EFFECT OF PHOSPHORUS FERTILIZATION AND Clitoria ternatea LEGUMINOUS GREEN MANURE ON THE GROWTH AND YIELD OF ARUMBA WAXY CORN (Zea mays Ceratina var. Arumba)] Food security and resilience can be achieved through diversifying local food products, for example waxy corn (Zea mays Ceratina). The potential yield of this commodity can be increased through fertilization, either chemically using phosphorus fertilizer or organically using Clitoria ternatea leguminous green manure. This study aimed to obtain the interaction between P fertilization and Clitoria ternatea leguminous green manure on the growth and yield of Arumba waxy corn. This study is a factorial experiment arranged based on a Randomized Block Design (RBD). The first factor is phosphorus fertilizing, consisting of 3 treatment levels; the second is Clitoria ternatea leguminous green manure fertilizing, consisting of 2 treatment levels. The results of the study showed that the combination of 50 kg/ha phosphorus fertilization and without Clitoria ternatea leguminous green manure gave the best results on plant length at 14, 21, and 28 DAP; stem diameter at 7 and 28 DAP, cob diameter with husk, cob weight with husk, cob weight without husk, and total fresh weight of Arumba waxy corn. The single treatment of P fertilization had a very significant effect on plant length at 35 DAP and stem diameter at 7 and 28 DAP, and had a significant impact on stem diameter at 35 DAP. Based on the results of the study, phosphorus fertilization at a rate of 50 kg/ha is recommended for the cultivation of Arumba waxy corn, as it resulted in the highest yield during the generative growth phase. Full text pdf